Empirical Investigation of the Efficiency of Heat Pipe Heat Exchanger as a Preheater in the Regeneration System of Liquid Calcium Chloride (CaCl2) - Fahlovi, Oldy; Avista, Zeluyvenca (Yayasan Ghalih Pelopor Pendidikan (Ghalih Foundation), 2024)
The use of air conditioning (AC) systems has greatly improved human comfort since the 20th century. However, challenges like the greenhouse effect, global warming, and increased energy consumption pose significant problems. To address these issues, a common solution is the use of desiccants to absorb air humidity, though regenerating them with a boiler requires additional energy. This study investigates the application of Heat Pipe Heat Exchanger (HPHE) to harness wasted heat as a preheating medium in a regeneration system. Solutions of calcium chloride (CaCl2) desiccants, ranging in concentrations of 36%, 49%, and 62%, coupled with flow rates of 0.1, 0.15, and 0.2 liters per minute, were employed to evaluate both the effectiveness and the visual quality of the regeneration system. Results showed the highest temperature difference with a 62% concentration desiccant at a flow rate of 0.15 liters/minute, approximately ±2.35°C. The regenerator and dehumidifier achieved peak effectiveness at a concentration of 62% and a flow rate of 0.2 lpm, recording values of 23.56% and 45.31%, respectively. This research proposes a practical solution for recovering wasted heat in AC regeneration systems, reducing energy consumption, and improving desiccant utilization efficiency.